Intergenerational altruism and transfers of time and money: a life cycle perspective - Uta Bolt; Eric French; Jamie Hentall-MacCuish; Cormac O'Dea (Institute for Fiscal Studies (IFS), 2023)
Parental investments significantly impact children's outcomes. Exploiting panel data covering individuals from birth to retirement, we estimate child skill production functions and embed them into an estimated dynastic model in which altruistic mothers and fathers make investments in their children. We find that time investments, educational investments, and assortative matching have a greater impact on generating inequality and intergenerational persistence than cash transfers. While education subsidies can reduce inequality, due to an estimated dynamic complementarity between time investments and education, it is crucial to announce them in advance to allow parents to adjust their investments when their children are young.
Keywords: 330; Intergenerational transmission; educational investment; time; educational returns; intergenerational equity; altruism; life cycle hypothesis; estimation; Great Britain; Intergenerationale Übertragung; Bildungsinvestition; Zeit; Bildungsertrag; Generationengerechtigkeit; Altruismus; Lebenszyklushypothese; Schätzung; Großbritannien